Answers

2014-07-21T18:12:50+05:30
P(x) = 3x^2-6x-1 = ax^2+bx+c=0
    α+β=-b/a=-(-6)/3=2
  α+β=2 --------------eqn(1)
now,
     αβ=c/a=-1/3 -------------eqn(2)
 we know that,      (α+β)^2-(α-β)^2=4*αβ
                           (2)^2-(α-β)^2=4*(-1/3)
                            4-(α-β)^2=-4/3
                            (α-β)^2=4+4/3
                             (α-β)^2=16/3
                              α-β  =  √(16/3)
                               α-β = +-4/√3    ----------------eqn(3)
eqn(1) + eqn(3)
2α = 2+-4/√3
α = 1+-2/√3
from eqn (1)
β=2-α
β=2-(1+-2/√3)
β=1+2/√3
when we put the value of α and β ,then we can find the value of 
α^2+β^2  , α^3+β^3, and α^3-β^3
0
Thank you so much Karthik4297!
bro hats off for ur typing
ook
Great Bro :)
thanks u frnds